Fisiologia de acessos de Jatropha curcas L. cultivados em solo contendo lama do Rio Doce - Santos Junior, Ramon Negrão (2018)
The objective of this work was to evaluate the effects of different concentrations of mud from the Doce River on Chlorophyll a fluorescence, gas exchange, pigment content and antioxidant enzyme activity, from five accessions of Jatropha curcas L. The mud was collected 15 months after the dam of Fundão/MG, and then the accesses NEF 04, NEF 05, NEF 09, NEF 12 and NEF 17, were submitted to three different concentrations of mud (0, 10 and 30 %). The measurements of Chlorophyll a fluorescence transient, gas exchange and pigment contents were performed monthly between November 2017 and March 2018. In this last month, measurements were made of modulated fluorescence, activity of antioxidant enzymes and of macro and micronutrient contents and As, Cd and Pb from leaves. The photochemical parameters that best evidenced the effects of the Doce River mud during plant development were the quantum yield of the electron transport of QA - to the electron acceptors of the intersystem (fE0), the probability (at t = 0) that an exciton captured has to move an electron in the electron carrier chain after the quinone a (?E0), the photosynthetic active reaction center density of photosystem II (RC/ABS), the performance index of photosystem II (PIabs) and the index of total performance (PItotal). The PIabs and PItotal presented an initial increase when conditioned to 30% of Doce River mud in the NEF 05, NEF 09 and NEF 12 plants, but this difference did not exist at the end of the experiment. No differences were observed between the control (0%) and 30% of the Doce River mud in modulated fluorescence, Chlorophyll content, liquid photosynthesis rate (A) and transpiration (E). However, there were alterations in catalase activity as a function of the different concentrations of mud in the plants of the NEF 04 and NEF 05 accessions. No significant levels of As, Cd and Pb were found in the leaves of Jatropha curcas L. in any of the evaluated accessions. However, in the individuals conditioned to 30% of Doce River mud, values of Fe above recommended levels were found, especially in NEF 12. These results demonstrate that Jatropha curcas L. have mechanisms that allow the bioaccumulation of Fe, and, they provide the tolerance in media containing the mud of the Doce River, after dam rupture.